Transcriptomic analysis of male and female Schistosoma mekongi adult worms - Orawan Phuphisut; Pravech Ajawatanawong; Yanin Limpanont; Onrapak Reamtong; Supaporn Nuamtanong; Sumate Ampawong; Salisa Chaimon; Paron Dekumyoy; Dorn Watthanakulpanich; Brett E. Swierczewski; Poom Adisakwattana (Parasites & Vectors, 2018)
Abstract Background Schistosoma mekongi is one of five major causative agents of human schistosomiasis and is endemic to communities along the Mekong River in southern Lao People’s Democratic Republic (Laos) and northern Cambodia. Sporadic cases of schistosomiasis have been reported in travelers and immigrants who have visited endemic areas. Schistosoma mekongi biology and molecular biology is poorly understood, and few S. mekongi gene and transcript sequences are available in public databases. Results Transcriptome sequencing (RNA-Seq) of male and female S. mekongi adult worms (a total of three biological replicates for each sex) were analyzed and the results demonstrated that approximately 304.9 and 363.3 million high-quality clean reads with quality Q30 (> 90%) were obtained from male and female adult worms, respectively. A total of 119,604 contigs were assembled with an average length of 1273 nt and an N50 of 2017 nt. From the contigs, 20,798 annotated protein sequences and 48,256 annotated transcript sequences were obtained using BLASTP and BLASTX searches against the UniProt Trematoda database. A total of 4658 and 3509 transcripts were predominantly expressed in male and female worms, respectively. Male-biased transcripts were mostly involved in structural organization while female-biased transcripts were typically involved in cell differentiation and egg production. Interestingly, pathway enrichment analysis suggested that genes involved in the phosphatidylinositol signaling pathway may play important roles in the cellular processes and reproductive systems of S. mekongi worms. Conclusions We present comparative transcriptomic analyses of male and female S. mekongi adult worms, which provide a global view of the S. mekongi transcriptome as well as insights into differentially-expressed genes associated with each sex. This work provides valuable information and sequence resources for future studies of gene function and for ongoing whole genome sequencing efforts in S. mekongi.